From field to factory : new industrial employees - Slotkin, James Sydney (Glencoe, Ill.: Free Press, 1960)
This book is one of the contributions to the "Inter-University Study of Labour Problems in Economic Development".
Bibliographical references
rpm 27/02/2018
Loans
Keywords: Personnel management; Industrial relations; Social adjustment